Performance ofintersynthetic hybrids generated from reciprocal recurrent selection. - Vasal, S. K. (2016)
The populations 21 (Tuxpeño) and 32 (Eto Blanco) are known to be heterotic and are being improved using a modified interpopulation improvement system. In this study, synthetics with 3, 6, 9 and 12 lines were developed from each population and then intercrossed in a design-2 mating system to generate 16 intersynthetic hybrids. The 16 intersynthetic hybrids, 8 parcntal synthetics, and a single cross hybrid entry as a control were evaluated in four localities in a 5 x 5 simple lattice design with 4 replications. The yield performance of synthetics from Eto and Tuxpeño involving 6- 12 lines and the 3-lines Tuxpeño synthetics was similar (5.8 - 6.3 t/ha). However, the 3-1ine Eto synthctic registered a marked decrease in yield (5.1 t/ha). The bettcr parent heterosis of intersynthetic hybrids ranged from 11.1 to 29.6%. Usually, crosses among synthetics involving a fewer lines resulted in higher heterosis compared to synthetic crosses involving more than 3 lines. The results suggest that intersynthetic hybrids formed from 6 - 9 lines seem more appealing considering the level of heterosis (>20.0%) and a high yield per se of parental varieties. The intersynthetic hybrids offer an attractive option for those national programs with newly initiated hybrid projects, for creating hybrid -oriented maize germplasm and inbred line development.